Sparse testing designs for optimizing predictive ability in sugarcane populations - Garcia-Abadillo, Julian; Adunola, Paul; Aguilar, Fernando Silva; Trujillo-Montenegro, Jhon Henry; Riascos, John Jaime; Persa, Reyna; Isidro y Sanchez, Julio; Jarquín, Diego (Frontiers in Plant Science, 2024)
Sugarcane is a crucial crop for sugar and bioenergy production. Saccharose content and total weight are the two main key commercial traits that compose sugarcane's yield. These traits are under complex genetic control and their response patterns are influenced by the genotype-by-environment (G×E) interaction. An efficient breeding of sugarcane demands an accurate assessment of the genotype stability through multi-environment trials (METs), where genotypes are tested/evaluated across different environments. However, phenotyping all genotype-in-environment combinations is often impractical due to cost and limited availability of propagation-materials. This study introduces the sparse testing designs as a viable alternative, leveraging genomic information to predict unobserved combinations through genomic prediction models. This approach was applied to a dataset comprising 186 genotypes across six environments (6 × 186 = 1,116 phenotypes). Our study employed three predictive models, including environment and genotype as main effects, as well as the G×E to predict saccharose accumulation (SA) and tons of cane per hectare (TCH). Calibration sets sizes varying between 72 (6.5%) to 186 (16.7%) of the total number of phenotypes were composed to predict the remaining 930 (83.3%). Additionally, we explored the optimal number of common genotypes across environments for G×E pattern prediction. Results demonstrate that maximum accuracy for SA () and for TCH ( ) was achieved using in training ρ = 0. 611 ρ = 0. 341 sets few (3) to no common (0) genotype across environments maximizing the number of different genotypes that were tested only once. Significantly, we show that reducing phenotypic records for model calibration has minimal impact on predictive ability, with sets of 12 non-overlapped genotypes per environment (72 = 12 × 6) being the most convenient cost-benefit combination.